Genetic diversity and spatial distribution of Hepatozoon spp. in domestic cats from Argentina - María Celeste Facelli Fernández; Florencia Facelli Fernández; Marcelo Signorini; Ana Molineri; Lucas Daniel Monje (Veterinary Research Communications, 2026)

Identification of risk factors associated with the presence of phthalates in raw milk obtained by manual and mechanical milking in Argentina - Pablo L. Pisano; Santiago A. Bortolato; Miguel Taverna; Marcelo Signorini; Dianela Costamagna (Food Control, 2026)

Patagonian shellfish and hidden threats: unveiling the viral landscape and the first quantitative microbial risk assessment of Argentine bivalve mollusks - Camila Frydman; Viviana Parreño; Mariana Cap; Solange Galeano; Marcelo Signorini Porchietto; Marina Mozgovoj (Food Microbiology, 2026)

Persistence of colistin-resistant Escherichia coli and the mcr-1 gene in the poultry chain, after the colistin ban - Florencia Aylen Lencina; Carolina Raquel Olivero; Jorge Alberto Zimmermann; María Ángeles Stegmayer; Noelí Sirini; Laureano Sebastián Frizzo; Lorena Paola Soto; Marcelo Lisandro Signorini; María Virginia Zbrun (Veterinary Research Communications, 2026)

Optimizing indirect selection of tropical wheat genotypes using high-throughput longitudinal phenotyping and trait relationships - Caique Machado e Silva; Victor Silva Signorini; Henrique Caletti Mezzomo; João Paulo Oliveira Ribeiro; Gabriel Wolter Lima; Marcelo Fagundes Portes; Lucas de Paula Corrêdo; Tiago Olivoto; Gota Morota; Maicon Nardino (Remote Sensing Applications: Society and Environment, 2026)

A spatiotemporal analysis of bovine brucellosis cases in dairy herds from Argentina, from 2014 to 2023 - María Belén Novoa; Nerina Patricia Aguirre; Estefanía Ugarte; Camila Nayla Foster; Ana Inés Molineri; Marcelo Lisandro Signorini; Alberto Martín Molina; Victor René Vanzini (Tropical Animal Health and Production, 2025)

Effect of NaCl reduction and/or replacement on the quality and safety of dry-fermented sausages: Systematic review and meta-analysis - María Ángeles Stegmayer; Noelí Estefanía Sirini; Lorena Paola Soto; Jorge Alberto Zimmermann; María Virginia Zbrun; Florencia Aylen Lencina; Marcelo Lisandro Signorini; Laureano Sebastián Frizzo (Meat Science, 2025)

Correction: Antimicrobial resistance in Escherichia coli isolates from dairy farms (Santa Fe province, Argentina) - Peña Agostina; Boidi Flavia Jaquelina; Welschen Nicolás; Cicotello Joaquín; Alvarado Wanda; Aliprandi Diego; Miotti Camila; Zbrun María Virginia; Suárez Archilla Guillermo; Lencina Florencia Aylen; Signorini Marcelo Lisandro; Cecilia Camussone María; et al. (Brazilian Journal of Microbiology, 2025)

Antimicrobial resistance in Escherichia coli isolates from dairy farms (Santa Fe province, Argentina) - Peña Agostina; Boidi Flavia Jaquelina; Welschen Nicolás; Cicotello Joaquín; Alvarado Wanda; Aliprandi Diego; Miotti Camila; Zbrun María Virginia; Suárez Archilla Guillermo; Lencina Florencia Aylen; Signorini Marcelo Lisandro; Camussone Cecilia María; et al. (Brazilian Journal of Microbiology, 2025)

Development and Bayesian analysis of a competitive inhibition ELISA for caprine brucellosis - Camila Nayla Foster; Nolly María Monzon; Marcelo Lisandro Signorini; María Natalia Aznar; Nerina Patricia Aguirre; Beatriz Susana Valentini; Victor René Vanzini; María Belén Novoa (Veterinary Immunology and Immunopathology, 2025)

Analysis of management factors influencing Anaplasma marginale transmission - Nicolás Morel; Mariano Mastropaolo; Susana Torioni de Echaide; Marcelo L. Signorini; Atilio J. Mangold; Maria E. Primo (Veterinary Parasitology, 2024)

Seroprevalence of Leptospira antibodies in dogs and cats from Santa Fe, a city in East-Central Argentina endemic for leptospirosis - Tamara Ricardo; Ludmila R. Bazán Domínguez; Lucila Beltramini; Yanina Prieto; Anahí Montiel; Leticia Margenet; M. Fernanda Schmeling; Yosena T. Chiani; Marcelo L. Signorini; M. Andrea Previtali (Preventive Veterinary Medicine, 2024)

Comparison of real-time PCR and nested PCR based on the HlyA gene for the detection of Listeria monocytogenes. Application on cheese samples - María V. Zbrun; Nadia Moreno; Cecilia M. Camussone; Marcelo L. Signorini; María E. Primo (Brazilian Journal of Microbiology, 2024)

Meta-analysis of the prevalence of norovirus and hepatitis a virus in berries - Camila Miotti; Marcelo Lisandro Signorini; Juan Martín Oteiza; Verónica Emilse Prez; Patricia Angélica Barril (International Journal of Food Microbiology, 2024)

Insights on multi-spectral vegetation indices derived from UAV-based high-throughput phenotyping for indirect selection in tropical wheat breeding - Caique Machado e Silva; Henrique Caletti Mezzomo; João Paulo Oliveira Ribeiro; Victor Silva Signorini; Gabriel Wolter Lima; Eduardo Filipe Torres Vieira; Marcelo Fagundes Portes; Gota Morota; Lucas de Paula Corredo; Maicon Nardino (Euphytica, 2024)

Stochastic modelling to predict a priori the potential outcomes of different control schemes against the cattle tick Rhipicephalus microplus - Camila Miotti; Nicolás Morel; Marcelo Lisandro Signorini; Santiago Nava (Veterinary Parasitology, 2024)

Bovine campylobacteriosis in heifer: pathogenesis study and insights in the conventional and molecular diagnosis in an experimental bovine model and field cases - Juan A. García; Pablo D. Farace; Andrea K. Gioffre; Florencia Romeo; Andrea Verna; María A. Mendez; Claudia Morsella; Juan F. Aller; Marcelo Signorini; Fernando A. Paolicchi (Veterinary Research Communications, 2024)

Lactic acid bacteria viability in different refrigerated food matrices: a systematic review and Meta‑analysis - Lorena P. Soto; Noelí E. Sirini; Laureano S. Frizzo; María V. Zbrun; Jorge A. Zimmermann; María J. Ruiz; Marcelo R. Rosmini; Gabriel J. Sequeira; Camila Miotti; Marcelo L. Signorini (Critical Reviews in Food Science and Nutrition, 2023)

Effects of lactic acid bacteria and coagulase-negative staphylococci on dry-fermented sausage quality and safety: Systematic review and meta-analysis - María Ángeles Stegmayer; Noelí Estefanía Sirini; María Julia Ruiz; Lorena Paola Soto; María Virginia Zbrun; José Manuel Lorenzo; Marcelo Lisandro Signorini; Laureano Sebastián Frizzo (Meat Science, 2023)

Quantitative microbial spoilage risk assessment caused by fungi in sports drinks through multilevel modelling - Félix G. Ramos Guerrero; Marcelo Signorini; Alberto Garre; Anderson S. Sant'Ana; Juan C. Ramos Gorbeña; Marcial I. Silva Jaimes (Food Microbiology, 2023)

Antimicrobial resistance of Streptococcus uberis isolated from bovine mastitis: Systematic review and meta-analysis - Camila Miotti; Joaquín Cicotello; Guillermo Suarez Archilla; Verónica Neder; Wanda Alvarado Lucero; Luis Calvinho; Marcelo Signorini; Cecilia Camussone; María Virginia Zbrun; Ana Inés Molineri (Research in Veterinary Science, 2023)

Seroprevalence and risk factors associated with bovine Leukemia virus infection in argentine beef cattle - Natalia Gabriela Porta; Guillermo Suarez-Archilla; Camila Miotti; Ana Inés Molineri; Irene Alvarez; Karina Trono; Marcelo Signorini; Vanesa Ruiz (Research in Veterinary Science, 2023)

Characterization of lesions of nutritional congenital goitre in cattle - Luis A. Colque-Caro; Francisco Acuña; Laura S. Aguirre; Agustín Avellaneda-Cáceres; Claudio G. Barbeito; Marcelo Signorini; Dadin P. Moore; Juan F. Micheloud (Journal of Comparative Pathology, 2023)

Leptospiral infection in domestic cats: Systematic review with meta-analysis - Tamara Ricardo; Lucía Azócar-Aedo; Marcelo Signorini; María Andrea Previtali (Preventive Veterinary Medicine, 2023)

Short communication: Varroa destructor re-invasion dynamics during autumn and winter in Apis mellifera colonies from a temperate climate - Agostina Giacobino; Camila Miotti; Ana Molineri; Emanuel Orellano; Marcelo Signorini; Adriana Pacini (Journal of Invertebrate Pathology, 2023)

Bovine campylobacteriosis in bulls: insights in the conventional and molecular diagnosis - Juan A. García; Pablo Farace; Andrea K. Gioffré; Claudia Morsella; María A. Méndez; Joaquín Acuña; Juan F. Aller; Marcelo Signorini; Fernando A. Paolicchi (Brazilian Journal of Microbiology, 2023)

Involvement of the serotonergic system in the antidepressant-like effect of 1-(phenylselanyl)-2-(p-tolyl)indolizine in mice - Marcia Juciele da Rocha; Camila Simões Pires; Marcelo Heinemann Presa; Evelyn Mianes Besckow; Gustavo D’Avila Nunes; Caroline Signorini Gomes; Filipe Penteado; Eder João Lenardão; Cristiani Folharini Bortolatto; César Augusto Brüning (Psychopharmacology, 2023)

Bidirectional movement of aphid parasitoids (Braconidae: Aphidiinae) between crops and non-crop plants in agroecosystems of central Argentina - Leticia Zumoffen; Marcelo Signorini; Adriana Salvo (Applied Entomology and Zoology, 2018)

Genotypic and phenotypic detection of capsular polysaccharide and biofilm formation in Staphylococcus aureus isolated from bovine milk collected from Brazilian dairy farms - Alessandra P.S. Salimena; Carla C. Lange; Cecilia Camussone; Marcelo Signorini; Luis F. Calvinho; Maria A.V.P. Brito; Cristiano A.V. Borges; Alessandro S. Guimarães; João B. Ribeiro; Letícia C. Mendonça; Roberta H. Piccoli (Veterinary Research Communications, 2016)

Laboratory and field studies to evaluate the potential of an open rearing system of Lysiphlebus testaceipes for the control of Aphis craccivora in Argentina - Leticia Zumoffen; Julia Tavella; Marcelo Signorini; Adriana Salvo (BioControl, 2016)

Reproductive success of the A rgentine anchovy, E ngraulis anchoita , in relation to environmental variability at a mid‐shelf front ( S outhwestern A tlantic O cean) - Marina Marrari; Sergio R. Signorini; Charles R. McClain; Marcelo Pájaro; Patricia Martos; María Delia Viñas; Jorge Hansen; Roxana Dimauro; Georgina Cepeda; Claudio Buratti (Fisheries Oceanography, 2013)
The mid‐shelf front ( MSF ) of the Buenos Aires province continental shelf in the Southwestern Atlantic Ocean plays a central role in the pelagic ecosystem of the region acting as the main spring reproductive area for the northern population of the Argentine anchovy E ngraulis anchoita and supporting high concentrations of chlorophyll as well as zooplankton, the main food of anchovy. To investigate the influence of environmental variability on the reproductive success of E . anchoita , we analyzed a 13‐yr time series (1997–2009) of environmental data at MSF including chlorophyll dynamics, as well as zooplankton composition and abundance, ichthyoplankton distributions, and recruitment of E . anchoita . Spring chlorophyll concentrations showed high interannual variability and were mainly influenced by changes in water temperature and vertical stratification, which in turn control nutrient supply to the surface. Chlorophyll dynamics (magnitude, timing, and duration of the spring bloom) explained most of the variability observed in E . anchoita recruitment, most likely via fluctuations in the availability of adequate food for the larvae. Our results suggest that satellite ocean color products can be valuable tools for understanding variability in ecosystem dynamics and its effects on the recruitment of fish.